A Survey Study to Indicate Contamination Ratio in Blood of Workers Run Generators in Baghdad City From Some Heavy Metals - Hussein, Huda Jabber (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The aim of this study was to measure the concentration of some heavy metals (Lead, Cadmium ,Iron and Cupper) in blood samples of workers who operate the diesel generator in Baghdad city(Dora, Harthya, Bayaa and Hay al Jameaa ) ,and their effects on Testosterone hormone. The study included two groups: the first control group consisted of 20 normal male (non workers and non smoking), and the second consisted of 20 male (generator workers). Blood samples were collected from each two groups, where each sample was divided into two parts, the first part estimated blood concentrations of heavy metals while the second tested testosterone. Data were treated statistically using (Statistical Analysis System 2012) program, and the averages of the studied values were compared by least significant difference (LSD) at the P< 0.05 level of probability.The results showed that the impact of exposure workers diesel generators for vapors emitted from generator exhausts have a high concentration of heavy metals which are significantly increased compared with the controlled group at probability of P <0.05,that significant difference was (0.351,0.133,0.358,1.276) for Lead, Cadmium, Cupper and Iron respectively which have significant effect on the testosterone hormone concentration that significant difference was (0.947) at the level of probability P< 0.05.